Phytoremediation: New Approaches and Perspectives - Bartucca, Maria Luce; Forni, Cinzia; Cerri, Martina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint brings together articles that have investigated certain aspects of phytoremediation or that have tested new methodologies related to this technique, helping to broaden the horizon of knowledge on a subject that is so important today.